Implementasi Etika Bisnis dan Kualitas Produk Pada Novel Rendez-Vous Di Angkringan Paijan Karya Kimberly Harjawinata - Retika Sari, Olivia; Narayanti, Luh; Kurniawan, Eva Dwi (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
Angkringan is a place for appointments for all groups. The angkringan owner, who heard all the conversations in his tent, ended up becoming a victim of fighting. Not only are they victims of fighting against each other, angkringan owners are faced with the problem of increasing prices for production materials. These two things cause angkringan traders to be able to maintain their business. This research uses a qualitative method with descriptive results and also uses a heuristic reading method, namely by reading thoroughly. The data source was taken from the novel "Rendez-Vous di angkringan paijan" by Kimberly Harjawinata and other data sources, namely books and journals that are appropriate to the topic under study. By being professional and applying ethics in business, angkringan traders have the trust of customers and suppliers. Suppliers will have more confidence in their customers to cooperate. Angkringan traders also have no problem making a small profit, because the main thing for angkringan traders is to be consistent in product quality, so customer satisfaction will also be met.